1994
DOI: 10.1007/bf02303530
|View full text |Cite
|
Sign up to set email alerts
|

Results of aggressive treatment of gastric sarcoma

Abstract: Curative gastric resection was achieved in 66% of patients and resulted in a significant prolongation of survival as compared with patients who had a palliative procedure. Wedge resection of tumor or partial gastric resection appears to be an acceptable surgical approach to these tumors as long as negative margins can be obtained. Chemotherapy, radiation therapy and debulking surgery did not result in significant prolongation of survival in the face of advanced disease. None of the staging systems for gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 9 publications
1
25
0
1
Order By: Relevance
“…Of 32 patients with gastric GIST, 41% presented with pain and 28% with GI bleeding. 37 Physical examination demonstrated a palpable mass in 12 of 32 patients. Thirty-nine small and large bowel GIST were identified at our institution.…”
Section: Managementmentioning
confidence: 99%
“…Of 32 patients with gastric GIST, 41% presented with pain and 28% with GI bleeding. 37 Physical examination demonstrated a palpable mass in 12 of 32 patients. Thirty-nine small and large bowel GIST were identified at our institution.…”
Section: Managementmentioning
confidence: 99%
“…Finally, two studies reported the effect of surgery on metastatic disease. 50,55 The results (Tables 10 and 11) observed in these intervention studies in general did not promise patient benefit. Seven studies reported median survival (range 8-24 months).…”
Section: Results Reported In Studies Of Alternative Treatmentsmentioning
confidence: 91%
“…Of the nine trials that measured tumour response, only one patient (unlikely to have a true GIST) had a complete response. 55 In terms of tumour response, 13 patients out of a total of 258 cases (5%) achieved a partial response, while 64 (24%) were described as having stable disease. Adverse events were only described in eight trials.…”
Section: Results Reported In Studies Of Alternative Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in adjuvant setting, the ef® cacy of radiotherapy and chemotherapy for sarcomas of gastrointestinal tract has not been well determined (10,11). The decrease in serum LDH levels immediately after the start of radiotherapy suggests that radiotherapy had a major effect in this recurrent tumor in our case.…”
mentioning
confidence: 74%